Cleaner production of rare earth elements from phosphorus-bearing sulfuric acid solution of vein deposit monazite. (1st January 2021) - Ilyas, Sadia; Kim, Hyunjung; Srivastava, Rajiv Ranjan; Choi, Sowon
Abstract: In the present study, the recovery of rare earth elements (REEs; viz. cerium, lanthanum, and yttrium) from sulfate leach liquor of vein deposit Korean monazite has been investigated using the solvo-chemical techniques. The dissolved phosphorus (373 mg L −1 ), which may significantly affect the products' purity, was selectively removed using the benzyl-di-methyl amine (BDMA). The logarithmic distribution vs. BDMA concentration along with spectral analysis of the organic phases revealed the formation of extracted species 3 [ BDMA ] . [ H 3 PO 4 ] ¯ . The quantitative removal of phosphorus was achieved in three stages of counter-current extraction (CCE) under the organic-to-aqueous (O:A) ratio of 1.0:1.5, leaving REEs' into the raffinate. Subsequently, Cyanex 923 was employed to selectively extract cerium(IV) from P-depleted solution under the varying parameters of extractant and sulfuric acid concentration, temperature, and O:A ratio. The quantitative extraction of cerium (∼99% from 864 mg L −1 feed concentration) showing exothermic nature was achieved at an O:A of 1:2 under three stages of CCE while using 0.15 mg L −1 extractant into organic phase and 1.12 mol L −1 H2 SO4 into aqueous phase. Further, the experimental results and spectral analysis of the organic phases could reveal that cerium solvates as [ Ce ( SO 4 ) 2 ] . 2 [ Cyanex  923 ] . [ HSO 4 − ] ¯ species. Cerium was successfully stripped from loaded organic by contacting with a higher concentration of H2 SO4 solution (≥4.0 mol L −1 ) in presence of 0.1 mol L −1 H2 O2, yielding an enriched high-purity solution of 2.54 g L −1 cerium. Lanthanum and yttrium were recovered from the Ce-depleted raffinate by co-precipitation with oxalic acid, forming a mixture of C6 La2 O12 .10H2 O and C6 Y2 O12 .4H2 O. The study approaches a cleaner production of high-purity REEs for clean energy programs under Sustainable Development Goals. Graphical abstract: Image 1 Highlights: P-bearing sulfate solution of vein deposit monazite was processed for REEs recovery. Phosphorus was prior separated using BDMA, leaving Ce, La and Y into the raffinate. Cyanex 923 potentially extracted Ce(IV) over La–Y(III) from P-depleted solution. La and Y were co-precipitated from Ce-depleted solution by oxalic acid treatment.